2005
DOI: 10.1002/elps.200500276
|View full text |Cite
|
Sign up to set email alerts
|

Mutation scanning-coupled analysis of haplotypic variability in mitochondrial DNA regions reveals low gene flow between human and porcineAscaris in endemic regions of China

Abstract: Haplotypic variation within and among the Ascaris populations representing six provinces in China was investigated. Mitochondrial DNA regions in the cytochrome c oxidase subunit 1 (cox1) and NADH dehydrogenase subunit 1 (nad1) genes were amplified by PCR from total genomic DNA samples (n > 720) from Ascaris individuals from humans and pigs, and subjected to mutation scanning and subsequent selective sequencing. For the cox1, ten different electrophoretic profiles were recorded for human Ascaris, and the same n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 41 publications
4
62
1
Order By: Relevance
“…Therefore, the aDNA analysis reported here falls short of confirming the Ascaris aDNA as A. lumbricoides. Many currently available nuclear or mitochondrial targets are not satisfactory for differentiating A. lumbricoides from A. suum (Anderson 2001, Peng et al 2005, Leles et al 2010, which stems from the close relationship between the two species (Barry & O' Rourke 1967, Crompton 1989, Zhu et al 1999, Leles et al 2010. This is again evident in our study because the differentiation between these two species was not achieved after genetic analysis.…”
Section: (Supplementary Data)mentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, the aDNA analysis reported here falls short of confirming the Ascaris aDNA as A. lumbricoides. Many currently available nuclear or mitochondrial targets are not satisfactory for differentiating A. lumbricoides from A. suum (Anderson 2001, Peng et al 2005, Leles et al 2010, which stems from the close relationship between the two species (Barry & O' Rourke 1967, Crompton 1989, Zhu et al 1999, Leles et al 2010. This is again evident in our study because the differentiation between these two species was not achieved after genetic analysis.…”
Section: (Supplementary Data)mentioning
confidence: 61%
“…In the case of ancient Ascaris spp, one of the most widespread parasitic infections in humans (Loreille & Bouchet 2003), PCR-based analyses have been performed and reported by Loreille et al (2001) and Leles et al (2008). However, even though Ascaris spp have been identified by molecular studies of archaeological specimens, their genetic diagnosis has not been studied in greater detail so far (Anderson 2001, Peng et al 2005, Leles et al 2010. Moreover, since most aDNA studies on Ascaris have been limited in their geographical distribution to Europe and South America, it is desirable to secure Ascaris aDNA data from a much wider geographic and temporal range.…”
mentioning
confidence: 99%
“…Application of a similar molecular approach to 115 sympatric worms obtained from humans and pigs in China (Peng et al, 1998) led to an analogous conclusion. This was later confirmed by the use of singlestrand conformation polymorphism (SSCP) to detect nucleotide variation in the internal transcribed spacer (ITS) region and mitochondrial cytochrome c oxidase subunit 1 (cox1) and NADH dehydrogenase subunit 1 (nad1) genes of 486 and 329 worms from humans and pigs, respectively, collected from six provinces in China (Peng et al, 2003(Peng et al, , 2005. Even though no fixed genetic differences were identified (i.e.…”
Section: Molecular Characterization Of Ascarismentioning
confidence: 94%
“…Sprent, 1952;Ansel and Thibaut, 1973;Maung, 1973;Kennedy et al, 1987;Hawley and Peanasky, 1992) but all with limited success. More recently the application of different DNA-based methods on sympatric Ascaris populations in Guatemala, China, and Uganda suggests that there is no or limited gene flow between worms infecting humans and pigs (Anderson and Jaenike, 1997;Peng et al, 2005;Nejsum et al, 2010) implying that there are two different populations (species). In contrast, Criscione et al (2007) identified 4 and 7% of sympatric worms as being hybrids suggesting that cross-infections take place in areas where humans and pigs live in close proximity.…”
Section: Worm Species and Zoonotic Aspectsmentioning
confidence: 99%